The impact of online forums in the Basic English Teaching-Learning process during semester I 2012 at the Foreign Language Department of the University of El Salvador - Palencia Tejada, Sandra Emérita
Currently, Internet applications such as blogs, web pages and online forums have played a significant role in education. Classes at the Foreign Language Department (FLD) have been traditional; however, in semester I-2012, it was created the “Basic English Forum” which proves that this kind of technology provides valuable resources creating better ways of teaching and learning. By using this innovational tool, the interaction is possible not only between teacher and student but also among classmates. They can find a partner who can help them to resolve their doubts and questions during their learning process improving the relations among teachers and students. Among the variety of technology applications that can be used for educational purposes, online forums are one of the best resources that can be taken into account in traditional classes.